Influence of homogeneous gas phase reactions in the partial oxidation of methane to methanol and formaldehyde in the presence of oxide catalysts - Baldwin, T; Burch, R; Squire, G; Tsang, S (1991)
The partial oxidation of methane to methanol and formaldehyde by reaction with air has been investigated at elevated pressures and temperatures both in the presence and in the absence of oxide catalysts. The results show that the maximum reproducible yield of formaldehyde obtained with oxide catalysts is around 2-3%. In the absence of any catalyst, it has been observed that yields up to 3.46% may be obtained at a pressure of 5 bar, using a methane/air ratio of 1: 5 at 625°C. It is concluded that there is an important gas phase contribution which needs to be taken into account when examining the catalytic oxidation of methane at moderate pressures. Reasons for the low yield of formaldehyde generally observed with catalysts are discussed, and the problems associated with the facile nature of gas phase radical reactions are considered. © 1991.